PENGARUH KUALITAS SISTEM DAN KUALITAS INFORMASI TERHADAP KEPUASAN PENGGUNA APLIKASI PELAYANAN ADMINISTRASI KEPENDUDUKAN “PAK DALMAN” DI KABUPATEN KENDAL - Aris Sugiantoro; Amni Zarkasyi Rahman (Journal of Management and Public Policy, 2026)
Digital transformation in public services encourages local governments to introduce technology-based service innovations to improve the quality of service to the public. The Kendal Regency Government developed the "Pak Dalman" population administration service application to facilitate the public in processing population documents online. However, in its implementation, various complaints were still found from users regarding the quality of the system and the quality of the information available in the application. This condition can affect the level of public satisfaction as service users. This study aims to analyze the effect of system quality (X1) and information quality (X2) on user satisfaction (Y) of the Pak Dalman application in Kendal Regency. This research method uses a quantitative approach with an explanatory research type. The research sample was determined by the Slovin formula of 100 users, using purposive sampling techniques and a Likert scale for data collection. Data were collected by distributing questionnaires to respondents and analyzed using descriptive statistical analysis and multiple linear regression analysis. Hypothesis testing used a partial t-test, a simultaneous F-test, and a coefficient of determination analysis. The results showed that system quality and information quality had a positive and significant effect on user satisfaction, both partially and simultaneously. System quality and information quality significantly influence user satisfaction with the Pak Dalman application by 83.4% based on the coefficient of determination test. These results indicate that the better the quality of the system and information provided, the higher the level of user satisfaction. Based on the research findings, it is recommended to improve the reliability of the system quality and to supplement and clarify the information available in the Pak Dalman application to optimize population administration services and increase public satisfaction.